Potential Role of GST-π in Lung Cancer Stem Cell Cisplatin Resistance - Wenjun Wang (Hindawi Limited, 2021)
Background. Cancer stem cells (CSCs) are responsible for tumorigenesis, chemoresistance, and metastasis. Chemoresistance is a major challenge in the management of lung cancer. Glutathione-sulphur-transferase-π (GST-π) plays an important role in the origin and development of various types of cancer by regulating the cellular redox balance. Recent investigations have demonstrated that GST-π is associated with the chemoresistance of lung CSCs (LCSCs). However, the mechanism of GST-π in lung cancer, particularly in LCSCs, remains unclear. The present study is aimed at exploring the potential role of GST-π in stemness and cisplatin (DDP) resistance of LCSCs. Materials and methods. In the present study, lung cancer cell spheres were established using the A549 cell line, which according to our previous research, was confirmed to exhibit characteristics of stem cells. Next, GST-π protein expression, apoptosis percentage, and intracellular reactive oxygen species (ROS) concentration in A549 adherent cells and A549 cell spheres were analyzed by western blotting and flow cytometry, respectively. Finally, DDP resistance, ROS concentration, and GST-π expression in LCSCs were analyzed following the interference with GST-π using DL-buthionine-(S,R)-sulphoximine and N-acetylcysteine. Results. The results revealed that GST-π was highly expressed in A549 cell spheres compared with A549 adherent cells and was associated with a decreased intracellular ROS concentration (both P<0.05). Regulating GST-π protein expression could alter DDP resistance of LCSCs by influencing ROS. Conclusion. These results suggested that GST-π may be important for LCSC drug resistance by downregulating ROS levels. These findings may contribute to the development of new adjuvant therapeutic strategies for lung cancer.